Efficacy of cisplatin-based combinations in chemoradiation therapy of cervical cancer - I Ya Bazaeva (Современная онкология, 2015)
Introduction. High incidence of stage III-IV cervical cancer and high recurrence rate after treatment causes scientific research of alternative approach in patient’s treatment. Objective - improvement results of treatment patients with locally advanced cervical cancer (LACC). Materials and methods. 101 patients with T2b-3bN0-1M0-1 cervical cancer (M1 - paraaortic lymph nodes metastases by radiologic exam) received concurrent chemoradiation therapy followed by adjuvant chemotherapy (CT). External-beam conformal radiation therapy (EBRT) on pelvic and regional lymph nodes 50 Gy (25 fractions) with weekly chemotherapy: arm A - cisplatin 20 mg/m2 + paclitaxel 30 mg/m2, arm В - cisplatin 20 mg/m2 + irinotecan 20 mg/m2, arm C - cisplatin 40 mg/m2. Brachytherapy 30 Gy (4 fractions) following ERBT. In arm A and В after chemoradiation therapy patient received 2 cycles of adjuvant CT: paclitaxel 175 mg/m2 + cisplatin 75 mg/m2 every 3 weeks or irinotecan 65 mg/m2 on day 1 and 8 + cisplatin 75 mg/m2 on day 1 every 3 weeks. Results. All regimens shows high efficacy: objective responses in arm A obtained 96,9%, in arm В - 100%, in arm C - 100%. Median overall survival (OS) and progression free survival (PFS) in all arms not obtained. PFS at 1 year was significantly improved in arm A and В versus arm C: IIIb stage (arm A vs arm C, p=0,036; arm В vs arm C, p=0,005), pelvic lymph node metastases (arm В vs arm C, p=0,013), low-differentiation tumors (arm В vs arm C, p=0,013). 1-year OS did not shows improvement. Toxicity of all three regimens was tolerable. Conclusions. Our regimens showed high efficacy and tolerable toxicity. Significantly improvement in 1-year recurrence rate in poor-prognostic group of patients obtained encouraging results. Pending of medians OS and PFS allows to make the final conclusion about the benefits of combination chemoradiation therapy with adjuvant chemotherapy in LACC.